1980
DOI: 10.1177/28.7.6156200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of proteoglycan monomer and link protein in the matrix of bovine articular cartilage: An immunohistochemical study.

Abstract: Using monospecific antisera and immunofluorescence microscopy, proteoglycan monomer (PG), and link proteins were demonstrated throughout the extracellular matrix of bovine articular cartilage. A narrow band of strong pericellular staining was usually observed for both molecules, indicating a pericellular concentration of proteoglycan monomer: this conclusion was supported by dye-binding studies. Whereas PG was evenly distributed throughout the remaining matrix, more link protein was detectable in interterritor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 0 publications
6
87
0
Order By: Relevance
“…Remarkably, chondroitinase ABC-treated and subsequently cultured explants were able to restore GAG content to native levels ( Figures 2B and 3), a finding similar to that in previous studies that demonstrated the ability of cartilage to restore proteoglycan content and organization within 4-10 days after enzymatic digestion by increasing the rate of proteoglycan synthesis (45)(46)(47)(48). Although chondroitinase ABC treatment stimulated sulfate incorporation in the superficial layer, the level of sulfate incorporation in the middle layer was similar to that of the untreated explants ( Figure 4A), despite marked GAG deposition ( Figure 2B).…”
Section: Discussionsupporting
confidence: 87%
“…Remarkably, chondroitinase ABC-treated and subsequently cultured explants were able to restore GAG content to native levels ( Figures 2B and 3), a finding similar to that in previous studies that demonstrated the ability of cartilage to restore proteoglycan content and organization within 4-10 days after enzymatic digestion by increasing the rate of proteoglycan synthesis (45)(46)(47)(48). Although chondroitinase ABC treatment stimulated sulfate incorporation in the superficial layer, the level of sulfate incorporation in the middle layer was similar to that of the untreated explants ( Figure 4A), despite marked GAG deposition ( Figure 2B).…”
Section: Discussionsupporting
confidence: 87%
“…Animals were exsanguinated by cardiac puncture and ‫ف‬ 50 ml of serum was obtained. For immunoassays, F(ab Ј ) 2 preparations were obtained by pepsin digestion of each antiserum, as previously described (51). The Fc portion and undigested IgG were removed by AH-Sepharose-Protein A chromatography (Pharmacia Fine Chemicals, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…The sections were stained with fluoresein-labeled rabbit anti-sheep IgG, diluted at 1/10 with PBS, for 30 minutes, and then washed in PBS as above. Cell cytoplasms were counterstained with eriochrome black (1150 dilution in PBS) and viewed for green and red fluorescence with a Zeiss Photomicroscope 111 (13). Sections from tissue cultured with or without '251-labeled cathepsin B were placed onto gelatincoated glass slides and then dipped in Ilford Nuclear Research Emulsion gel and stored frozen at -20°C.…”
Section: Methodsmentioning
confidence: 99%